Konservatisme vs. Moderatisme: Kontestasi Pemikiran Keagamaan Kontemporer di Kalangan Ormas Islam Lokal di Madura, Indonesia - Hannan, Abd; Syarif, Zainuddin (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
This article discusses the notions of conservatism and religious moderatism through case studies of two contemporary Islamic organizations in Madura, Indonesia, namely Forum Kiai Muda Madura (FKM) and the Gerakan Santri-Pelajar Rahmatan Lil'alamin (GESPER) in Madura, Indonesia. These two mass organizations are part of the contemporary religious reality that significantly influences the religious dynamics of the Madurese community in Indonesia. This article uses qualitative research methods and Michel Foucault's theory of power relations. This study finds three findings. First, FKM and GESPER are local Islamic organizations in Madura that were both born and driven by a pesantren community consisting of Kiai, Lora, and santri. Second, based on its understanding and thoughts, the Islamic mass organization FKM's conservative religious view tends to be textual and exclusive. This mass organization is filled by the pesantren community outside the organizational structure of Nahdhlatul Ulama (NU), but culturally identify as adherents of NU. Meanwhile, the Islamic mass organization GESPER is an Islamic group that puts forward the values of moderation and tends to be dynamic and inclusive. Included in this line are the Islamic boarding schools, which are active in the organizational structure of NU in Madura. Third, although both were born in Islamic boarding schools, the two are often involved in friction due to differences in addressing contemporary Islamic social issues. This friction includes socio-religious issues that are thought-provoking, such as the discourse of Islam Nusantara, and practical socio-religious issues that are related to political themes, both at local and national levels